Deployment Experiences of Guard and Reserve Families Implications for Support and Retention - Werber, Laura (RAND Corporation, 2008)
Use of the Reserve Component has steadily increased since the 1990s, but little research has focused on how deployment affects guard and reserve families. This monograph presents the results of interviews with reserve component personnel and spouses, focusing on their deployment experiences and military career intentions. The authors conclude with suggestions on how the Department of Defense can better support guard and reserve families.